The Influence of Training, Career Development, and Compensation on Employee Retention at PT. Seiwa Indonesia - Yuniana, Selva; Hanafia, Fifi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
To achieve success in increasing employee retention, companies must pay attention to several factors, including providing appropriate training to employees, providing career development, and providing appropriate compensation so that they feel cared for by the company and provide their best performance to the company. The purpose of this research is to determine the effect of training, career development, and compensation on employee retention at PT Seiwa Indonesia. Data collection was carried out utilizing observation and questionnaires. The sampling technique was simple random sampling using the Slovin formula with a sample of 87 people in the population. This research uses quantitative methods using validity tests, reliability tests, multicollinearity tests, heteroscedasticity tests, multiple regression tests, t-tests, and F tests with the help of SPSS statistics. Based on the test results using the t-test, it shows that compensation partially has a positive and significant effect on employee retention, while job training and career development have no effect on employee retention, the test results using the F test show that job training, career development and compensation simultaneously have a positive effect on employee retention, the results of testing the coefficient of determination on the Adjusted R Square (R2) variables of job training, career development, and compensation can explain the magnitude of the influence of product quality, promotion and price on customer satisfaction of 61.5% while 38.5% is influenced by other factors.